Nisya:

The first thing I would do is "unravel" the factored expressions on each side of the equation, by multiplying out each side, as follows:

**(x-1)**^{2}=(x-2)^{2}

**x**^{2}-2x+1=x^{2}-4x+4

Next (by subtracting) I would bring all the terms with x to the left side and all non-x terms to the right side as follows:

**x**^{2}-x^{2} -2x+4x = 4-1

** 0 + 2x = 3**

** 2x = 3**

Finally solve for x, by dividing both sides by 2 to get:

**x=3/2**

You can check you work, by plugging 3/2 in for the value of x in the original expression:

**(x-1)**^{2}=(x-2)^{2}

**(3/2-1)**^{2}=(3/2-2)^{2}

**(3/2-2/2)**^{2}=(3/2-4/2)^{2}

**(1/2)**^{2}=(-1/2)^{2}

**1/4=1/4 (check!)**

Goo Luck!

George

## Comments